Poultry offal meal in chicken: Traceability using the technique of carbon (C-13/C-12)- and nitrogen (N-15/N-14)-stable isotopes - Cruz, V. C. [UNESP]; Araujo, P. C. [UNESP]; Sartori, José Roberto [UNESP]; Pezzato, Antonio Celso [UNESP]; Denadai, J. C.; Polycarpo, G. V. [UNESP]; Zanetti, L. H. [UNESP]; Ducatti, Carlos [UNESP] (Poultry Science Assoc Inc, 2012)
Studies on the detection of animal by-products in poultry meat are rare and practically nonexistent in chicken meat. With the development of the technique of stable isotopes for traceability purposes and the certification of broiler diet patterns, it has been necessary to know the behavior of the isotopic signature of different tissues in birds, in case of a potential replacement of a diet containing animal ingredients with a strictly vegetable one and vice versa. Thus, this study, carried out at the São Paulo State University, Botucatu Campus, Brazil, aimed to evaluate meat from the breast, thigh, drumstick, and wings to trace the presence of poultry offal meal (OM) in broiler feed using the analysis of stable isotopes of carbon (C-13/C-12) and nitrogen (N-15/N-14) by mass spectrometry. In total, 720 one-d-old chicks were distributed into 6 groups: vegetable diet (VD) from 1 to 42 d; 8% poultry offal meal (OM) diet from 1 to 42 d; VD from 1 to 21 d and 8% OM diet from 22 to 42 d; VD from 1 to 35 d and 8% OM diet from 36 to 42 d; 8% OM diet from 1 to 21 d and VD from 22 to 42 d; and 8% OM diet from 1 to 35 d and VD from 36 to 42 d. Through the analysis of C and N, it is possible to trace the use of OM in broiler feeding when this ingredient is part of the feeding throughout the breeding phase or when it substitutes a strictly VD even up to 35 d. When an OM diet is substituted by a VD, the animal ingredient has to be part of the feeding for 21 d or longer to be detected by this method.
Keywords: animal origin ingredient; carbon-13; certification; nitrogen-15; poultry